RANCANGAN SISTEM APLIKASI PERIZINAN ONLINE UNTUK CV. EUROMAIR MENGGUNAKAN FRAMEWORK CODEIGNITER DAN BOOTSTRAP - Dwi Kartinah (Asosiasi Dosen Muda Indonesia, 2023)
Website is a document that sent into webserver and have various topics and kind. Website consist of two, i.e. static website and dynamic website. Static website is website where the user can’t modify the content of the web directly using browser. Meanwhile in dynamic website, interaction between user and server very complex. Someone can modify content of certain page using browser. This website application are built with PHP, CSS, HTML and javascript programming language with Codeigniter 3.0.6 and Bootstrap 3.3.6 framework. This application is made to help CV. Euromair employee to submit permission and leave. This research using method Waterfall model that consist of a few steps i.e. requirements planning and analysis, system design, implementation, testing, operation and maintenances. Application divide into two design i.e. administrator application and employee application. Based on implementation and testing result showed that this application run well and display all pages.